Iron absorption, localization, and biomineralization of Cynodon dactylon, a perennial grass from the Río Tinto basin (SW Iberian Peninsula). Issue 6 (25th October 2013) - Franco, Alejandro; Rufo, Lourdes; Rodríguez, Nuria; Amils, Ricardo; de la Fuente, Vicenta
Abstract Cynodon dactylon (L.) Pers. is a perennial rhizomatous grass (Poaceae), grown for cattle nutrition on the riverbanks of Río Tinto (Southwest Iberian Peninsula, Spain), a highly acidic area with high concentrations of iron (Fe) and other metals. This study focuses on the absorption, distribution, and accumulation of Fe in the root, rhizome, and leaves of C. dactylon under controlled conditions. Plants collected from Río Tinto were grown in a Hoagland solution containing 500 mg kg–1 of ferrous Fe. Samples were collected up to 2 months after exposure and analyzed for total Fe concentration using inductively coupled plasma–mass spectrometry (ICP‐MS) and for Fe distribution and bioformations by scanning electron microscopy (SEM) with an energy‐dispersive x‐ray analyzer (EDX). The results show high concentrations of Fe in all plant organs, with fast Fe translocation from roots to leaves. Iron bioformations composed mainly of Fe, S, and K were detected in all plant organs and were especially apparent in roots and leaves. These results differ from those reported for another species of Poaceae, Imperata cylindrica, which grows under the same environmental conditions, suggesting the existence of different resistance strategies between species of the same family.